Analisis Medan Semantik Kosakata Kenikmatan Surga Dalam Al-Qur'an Pada Surat Ar-Rahman dan Al-Waqi'ah - Siti Nurafriyani; Hadian Rizani; Ahmad Habibi Syahid (Universitas Muhammadiyah Surabaya, 2026)
This study aims to reconstruct a systematic semantic map of the concept of na'īm al-jannah (the pleasures of paradise) in Surat Ar-Rahman and Surat Al-Waqi‘ah using Jost Trier’s Semantic Field Theory. The Quranic description of paradise offers vivid sensory imagery; however, previous interpretations often analyze related vocabulary separately, lacking a comprehensive understanding of the semantic structure. Employing qualitative library research, this study identifies vocabulary related to the pleasures of paradise, categorizes them into thematic semantic subfields, and analyzes lexical relationships. The results show that the concept of heavenly pleasure is arranged in a precise semantic field system, comprising 34 lexemes across food, furniture, environment, and service sub-fields. A significant macro-structural difference was found: Surat Ar-Rahman applies a Duality pattern reflecting the balance of mercy, while Surat Al-Waqi‘ah applies a Hierarchy pattern emphasizing rewards based on deeds. This study proves that these sensory descriptions are a taqrib al-fahm strategy to approximate the abstract reality of paradise into human cognition. Keywords: Semantic field theory, Quranic semantics, pleasures of paradise, Surat Ar-Rahman, Surat Al-Waqi‘ah